Smart Shape‐Memory Polymeric String for the Contraction of Blood Vessels in Fetal Surgery of Sacrococcygeal Teratoma. Issue 13 (23rd April 2022) - Fulati, Ailifeire; Uto, Koichiro; Iwanaga, Masanobu; Watanabe, Miho; Ebara, Mitsuhiro
Abstract: Shape‐memory polymers (SMPs) are promising materials in numerous emerging biomedical applications owing to their unique shape‐memory characteristics. However, simultaneous realization of high strength, toughness, stretchability while maintaining high shape fixity ( R f ) and shape recovery ratio ( R r ) remains a challenge that hinders their practical applications. Herein, a novel shape‐memory polymeric string (SMP string) that is ultra‐stretchable (up to 1570%), strong (up to 345 MPa), tough (up to 237.9 MJ m −3 ), and highly recoverable ( R f averagely above 99.5%, R r averagely above 99.1%) through a facile approach fabricated solely by tetra‐branched poly( ε ‐caprolactone) (PCL) is reported. Notably, the shape‐memory contraction force (up to 7.97 N) of this SMP string is customizable with the manipulation of their energy storage capacity by adjusting the string thickness and stretchability. In addition, this SMP string displays a controllable shape‐memory response time and demonstrates excellent shape‐memory‐induced contraction effect against both rigid silicone tubes and porcine carotids. This novel SMP string is envisioned to be applied in the contraction of blood vessels and resolves the difficulties in the restriction of blood flow in minimally invasive surgeries such as fetoscopic surgery of sacrococcygeal teratoma (SCT). Abstract : A novel shape‐memory polymeric string is designed with simultaneous realization of high strength, toughness and deformability while maintaining excellent shape‐memory properties by simple manipulation of its energy storage capacity. The strong shape‐memory contraction effect is expected to be promising in the contraction of blood vessels during minimally invasive fetoscopic surgeries.